Just Google it: measuring schools' use of research evidence with internet search results. (1st February 2019) - Neal, Zachary; Lawlor, Jennifer; Watling Neal, Jennifer; Mills, Kristen; McAlindon, Kathryn
Abstract : Measuring the use of research evidence (URE) by schools has become a central focus of education researchers. However, it has proven challenging due to low response rates, social desirability bias, and costly or time-consuming data collection methods. To overcome these challenges and meet the needs of research focused on URE, this paper introduces a non-reactive archival measure: Archival Search of Use of Research Evidence (ASURE). ASURE counts references to research or evidence on a school's or school district's website to capture the extent of its rhetorical use of research evidence. After illustrating the collection of ASURE in all public school districts in Michigan (N = 595), we use data on these districts to show that ASURE is reliable and valid, and thus offers a promising new strategy for measuring URE in schools. We conclude by considering future steps for exploring ASURE, not simply as a measure of URE in schools, but instead as a measurement strategy for assessing URE in a broad range of organisational contexts.